TPACK Acceptance Level of Elementary Teachers in an Inclusive Education: A Correlational Study - Dulos, Claudee Jade; Macan, Denise Pauline E.; Playda, Jardine M.; Quezada, Rodeth Jane C. (International Journal of Research in Interdisciplinary Studies, 2025)
Educators worldwide are increasingly challenged to create learning environments that foster the engagement and achievement of every student, while also harnessing the potential of technology to enhance teaching and learning experiences. This research aims to determine the ascertain importance of primary school instructors to recognize the role that TPACK plays in inclusive education. The study employed a correlational research design and was participated by 150 elementary school teachers in Davao del Sur with the use of questionnaires. Likert scale option, Mean, and frequency distribution were utilized as statistical tools. The results of the study shows that elementary teachers in Davao del Sur demonstrate a high level of TPACK acceptance, particularly in terms of digital literacy, which scored the highest among the indicators. This suggests that most primary teachers are technologically inclined and open to integrating digital tools into their instructional strategies. However, the researchers recommend that the educational institutions must prioritize the enhancement of TPACK competencies among elementary teachers, with particular focus on teaching experience.